2018
DOI: 10.1042/bcj20180123
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD

Abstract: Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Cellular verification demonstrated that GBP1 and ETV7 may act as tumor suppressors in HGSOC, whereas CXCL13 may promote cell proliferation and migration. These findings are consistent with those of previous studies, although the functions of GBP1 and ETV7 in different tumors are controversial [ 21 , 22 , 34 , 35 ]. Moreover, we conducted immunohistochemistry (IHC) experiments to assess the expression of GBP1.…”
Section: Discussionsupporting
confidence: 93%
“…Cellular verification demonstrated that GBP1 and ETV7 may act as tumor suppressors in HGSOC, whereas CXCL13 may promote cell proliferation and migration. These findings are consistent with those of previous studies, although the functions of GBP1 and ETV7 in different tumors are controversial [ 21 , 22 , 34 , 35 ]. Moreover, we conducted immunohistochemistry (IHC) experiments to assess the expression of GBP1.…”
Section: Discussionsupporting
confidence: 93%
“…Recent data indicated that the GBP1-mediated anti-proliferative effects on human colorectal cancer cells DLD1 are mediated by a specific amino acid sequence at the N-terminus of the GBP1-α9-helix, which interacts with the DNA-binding domain of the transcription factor TEA Domain protein (TEAD). In this way, GBP1 inhibits TEAD transcriptional activity and down-regulates TEAD-target genes [51]. The role of GBP1 in EOC is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GBP1 has onco-protective effects beyond direct actin remodeling. Other cytoskeletal-independent activities include interactions between the GBP1 C-terminal domain and Hippo signaling transcription factor TEA domain protein that interferes with expression of YAP1–TEA domain protein target genes needed for cellular hyper-proliferation (Unterer et al, 2018). This may provide some basis for the ability of GBP1 to act as a tumor suppressor in colorectal cancers which arise from dysregulated Hippo signaling (Britzen-Laurent et al, 2013; Hong et al, 2016).…”
Section: Gbps In Oncogenic Surveillance and Cancermentioning
confidence: 99%